"Job Satisfaction in Saudi Universities For Non-Saudi Faculty Members: Applied Study of College of Business Administration Northern Borders University" - Ibrahim, Ahmed (The Arab Journal of Administration, 2022)
Universities are considered one of the most important institutions that play an important role in the development process as it is a scientific and academic organizational structure that makes more social and economic changes in society for the better depending on faculty members who consider human capital in these institutions. In finding skilled manpower locally or regionally, which leads them to search for qualified workers and talents in other countries and this leads to a cultural diversity in the organization as a result of these employees of different nationalities which leads to a multi-cultural environment This study aims to identify the factors of job satisfaction among non-Saudi faculty members in the Faculty of Business Administration, Northern Borders University. The basic components of 32 elements were the total variance of the four factors extracted through the statistical program explains 82.483 and the first factor is the work environment and nature of work which explains 33.050 of the cumulative ratios 82.483 and the second factor is the attendance of the seminars and conferences and research work and opportunities for promotion and grant rewards which explains the ratio of 18.926. Consequently, the third factor related to the relationship between members in the work environment, which explains the rate of 17.340, then comes the last factor, which is related to the sense of accomplishment and gaining experience, which explains the ratio of 13.167 of the cumulative ratios 82.483. These factors, the study concluded, recommended a set of recommendations to enhance the job satisfaction of non-Saudi faculty members in Saudi universities.